KEEFEKTIFAN MODEL PEMBELAJARAN TIPE TEAM ASSISTED INDIVIDUALIZATION DENGAN PENDEKATAN PROBLEM BASED LERNING TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK PADA MATERI BANGUN DATAR KELAS VII - Agnes Pratiwi; Martyana Prihaswati; Abdul Aziz (Universitas Muhammadiyah Semarang, 2017)
This research aims to determine the effectiveness of Teaching Model Type Assisted Individualization Model with Problem Based Learning approach toimproving the problem solving skills of students in the class of flat VII buildingmaterials. This research is an experimental research. The sample in thisresearch is VII E (experiment) and VII F (control). The results showed that: (1)learners using learning model Team Assisted Individualization Type WithProblem Based Learning Approach achieved mastery of 80.55% more than75% with complete criterion 75, (2) test results influence motivation andresponsibility to the ability of problem solving has a great influence of 84.4%,(3) the difference test results show the difference of the average value of theexperimental class problem solving ability of 78.28 is better than the controlclass of 68.90, (4) the improvement test results show the problem solving abilityof the class experiments increased with a gain value of 0.618 in the mediumcategory. Based on these four things, it shows that the learning model of TeamAssisted Individualization Type with Problem Based Learning Approach toImproving Student Problem-solving Ability of Class VII Building MaterialDeveloping Material is effective.Keywords: Team Assisted Individualization, Problem Based Learning, ProblemSolving